2001
DOI: 10.1520/jfs15011j
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Insect Succession and Pig Carcass Decomposition in a Natural Forest Area in Southeastern Brazil

Abstract: In this study, successional patterns, relative abundance of larvae and adults of sarcosaprophagous insects, carcass decay, diversity and seasonality of species, and their potential as forensic indicators were studied. Four experiments were carried out in each season in a natural area of southeastern Brazil. Two pigs (Sus scrofa L.) were used in each experiment and were exposed to sunlight and shade, respectively. The Calliphoridae outnumbered the Sarcophagidae in specimens collected and reared from the carcass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
3
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(45 citation statements)
references
References 13 publications
5
27
3
10
Order By: Relevance
“…The nose and mouth emit odours that attract flies and are therefore often the first areas to be colonised by insects [16]. This is in line with the observations made in a study by Lopes de Carvalho [20], with the Diptera (Calliphoridea) more abundant during the earlier stages of decomposition, whereas the omnivorous species were predominant during the later stages of decomposition. In the current study, similar oviposition was observed on carcasses irrespective of size and weight.…”
Section: Resultssupporting
confidence: 77%
“…The nose and mouth emit odours that attract flies and are therefore often the first areas to be colonised by insects [16]. This is in line with the observations made in a study by Lopes de Carvalho [20], with the Diptera (Calliphoridea) more abundant during the earlier stages of decomposition, whereas the omnivorous species were predominant during the later stages of decomposition. In the current study, similar oviposition was observed on carcasses irrespective of size and weight.…”
Section: Resultssupporting
confidence: 77%
“…The number of specimens collected was considered satisfactory and unaffected by the rains during the period of experimentation, which differs from the results found by Eberhardt and Elliot [9], who noted the lowest visitation rates to open-air exposed carcasses and a subsequent deceleration of decomposition during the rainy season. Similar results were published by Lopes de Carvalho and Linhares [33], whose study also coincided with greater rainfall and higher temperatures; thus the decomposition was rapid and intense. The flies were classified as belonging to 11 families, and 27 species were identified from the families with the greatest forensic interest (Calliphoridae, Muscidae, Fanniidae, and Sarcophagidae) ( Table 2).…”
Section: Sp-ssupporting
confidence: 90%
“…Similar to the methods used by Eberhardt and Elliot [9], the fresh phase was calculated from the moment of swine death until the early bloat phase. As expected, less than a month was required for the carcasses to reach total decomposition, which differs from the results found by Martinez et al [8], who found that the carcass decomposition process required 83 days, and those of Lopes de Carvalho and Linhares [33], who conducted a study during the wet season and found that casting decomposition required 45 days. To verify the decomposition phases and climatological monitoring, a standard 30 days of observation was followed in the present study.…”
Section: Resultscontrasting
confidence: 65%
“…En el año 2000, López y col. [13], en el estado de Sao Paûlo al sur-este de Brasil, realizaron un estudio donde se emplearon dos cadáveres de esta especie de cerdo, de 10 Kgs. de peso aproximadamente, los cuales fueron colocados en un área boscosa densa, con una separación de 40 metros, uno del otro, quedando un cadáver expuesto a la luz solar y el otro en la sombra total.…”
Section: Discussionunclassified
“…Cabe destacar que de acuerdo con la colecta de insectos carroñeros hallados en un cadá-ver de cerdo en un área boscosa natural al sureste de Brasil reportado por López y col. [13], Chrysomia albiceps (orden Díptera, familia Calliphoridae) fue la especie más abundante en todos los experimentos. De un total de 14.113 especimenes de insectos adultos representados en 36 fami-lias, 85% pertenecían al orden Díptera y 12% al orden Coleóptera.…”
Section: Discussionunclassified